EKSISTENSI KEPERCAYAAN KERAMAT MONENG IMAM DALAM KEBUDAYAAN MASYARAKAT MUARA NILAU KECAMATAN SELANGIT KABUPATEN MUSI RAWAS - Sari, Inang; Sarkowi; Wulansari, Ratna (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This study aims to describe how the existence of the sacred belief of Moneng Imam in the culture of the Muara Nilau community, Selangit District, Musi Rawas Regency. The method used by the author is the historical method (history) with a qualitative approach. The research procedure uses Heuristics (Source Collection), Verification (Source Criticism), Interpretation (Interpretation), and Historiography. The results of the study are the existence of the sacred belief of Moneng Imam in the culture of the Muara Nilau community, Selangit District, Musi Rawas Regency, namely the community strongly believes in the sacred tomb, namely the Tomb of Moneng Imam and has been cultured and passed down from generation to generation. However, not all people believe in this, many also do not believe that the Tomb of Moneng Imam can help and answer prayers. The belief in Moneng Imam in Muara Nilau Village, Selangit District, Musi Rawas Regency, is not just an old story but a vibrant cultural phenomenon that continues to resonate in the lives of the local community. This sacred belief is deeply rooted because it serves as a spiritual, social, and identity pillar for the community. Moneng Imam has transformed into a cultural centre of gravity, whether as a legendary historical figure or a purely spiritual symbol. Through pilgrimage practices, rituals, vows, and oral narratives that are continually passed down, the people of Muara Nilau not only preserve the memory of this figure but also reproduce and strengthen their value system and worldview. This belief provides a sense of security, hope, and moral guidance, helping people face life's challenges in a way that aligns with their beliefs. The synthesis of local Islamic teachings and ancestral traditions is a hallmark of the Moneng Imam belief, demonstrating how cultures can adapt and create a unique harmony. In short, Moneng Imam is more than a tomb or a legend; it is a spiritual and social foundation that continues to shape and bind the culture of the Muara Nilau community to this day. Its survival underscores the crucial role of sacred beliefs in maintaining the cohesion and sustainability of a community amidst the changing times.